A meta-analysis of industry 4.0 design principles applied in the health sector. (September 2021) - Sisodia, Amrita; Jindal, Rajni
Abstract: The approach of health 4.0 is driven out from the well-known industry 4.0. The goal of industry 4.0 is to bring a revolution in the manufacturing sector by digitization. The future of health management will become timelier and more personalized as new technologies will empower individuals to conduct their health monitoring by using cyber–physical systems. The design principles of industry 4.0 connect the physical and virtual world in real-time. Virtualization in health happens after the emergence of Information and Communication Technologies (ICT). For this 5G, the next-generation mobile network provides ambient intelligence for orchestration of medical services so that government and private companies can reconsider health prospects. These technological developments in healthcare, big data and industry 4.0 are individually attracting the huge attention of academics and industries. However, a detailed study of big data and industry 4.0 together concerning healthcare is still not present in the existing literature. The main contribution of this article is to present a meta-analytic approach to interpret, integrate and critically investigate the findings of original articles. This study expounds a novel approach for achieving effectual and comparable results related to the explained research problems. The results summarize about the standards used in main research directions, and existing deficiencies present in this area. The findings of this systematic literature review (SLR) can be helpful as future guidelines to researchers and practitioners working in the area of health 4.0 and related topics. Highlights: Study of health 4.0 done by using Industry 4.0. Explanation of the designing principles of health 4.0. Explanation of the supportive technology of health 4.0. Formation of different RQs. Formation of e-Health architecture.